2022
DOI: 10.3390/molecules27123883
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical CO2 Extract from Microalga Tetradesmus obliquus: The Effect of High-Pressure Pre-Treatment

Abstract: High-pressure pre-treatment followed by supercritical carbon dioxide (ScCO2) extraction (300 bar, 40 °C) was applied for the attainment of the lipophilic fraction of microalga Tetradesmus obliquus. The chemical profile of supercritical extracts of T. obliquus was analyzed by ultra-high-performance liquid chromatography–high-resolution mass spectrometry with electrospray ionization (UHPLC-ESI-HRMS). Moreover, the impact of ScCO2 on the microbiological and metal profile of the biomass was monitored. The applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…Loliolide, the only monoterpernoid lactone detected in our study, was previously detected in C. spongiosus f. verticillatus by El Hattab et al [57]. It has also been detected in the genus Ericaria [28], D. vermicularis [40], and the microalga Tetradesmus obliquus [63]. Silva et al [64] demonstrated the neuroprotective, anti-inflammatory, and antioxidant effects of loliolide in an extract of Codium tomentosum.…”
Section: Non-target Screening Of Non-volatile Compounds In Ethanol Ex...supporting
confidence: 76%
“…Loliolide, the only monoterpernoid lactone detected in our study, was previously detected in C. spongiosus f. verticillatus by El Hattab et al [57]. It has also been detected in the genus Ericaria [28], D. vermicularis [40], and the microalga Tetradesmus obliquus [63]. Silva et al [64] demonstrated the neuroprotective, anti-inflammatory, and antioxidant effects of loliolide in an extract of Codium tomentosum.…”
Section: Non-target Screening Of Non-volatile Compounds In Ethanol Ex...supporting
confidence: 76%
“…17, 21, 24) and two diacylglycerols (no. [32][33] showed an increase in the N-deprived samples. A long-chain fatty acid C:20 (no.…”
Section: Non-target Screening Of Non-volatile Compounds In Ethanol Ex...mentioning
confidence: 89%
“…Menzel et al [31] used it as a biomarker in haptophytes, diatoms, dinoflagellates, and eustigmatophytes while investigating the deposition of sapropel. Loliolide was detected in acetone and MeOH extracts of the Antarctic diatoms Craspedostauros ineffabilis and C. zucchelli, as well as in a supercritical CO 2 extract of the green microalga Tetradesmus obliquus [32]. In the Ndeprived sample, it was 1.2 times more abundant than in the control sample, 1.8 times more than in the P-deprived sample and 5.0 times more than in the Si-deprived sample.…”
Section: Non-target Screening Of Non-volatile Compounds In Ethanol Ex...mentioning
confidence: 95%